Change of the forest cover on the slopes oriented towards Lake Imandra lake under industrial pollution - Черненькова, Татьяна Владимировна; Королева, Наталья Евгеньевна; Басова, Елена Викторовна; Боровичев, Евгений Александрович; Мелехин, Алексей Валерьевич; Chernenkova, Tatiana; Koroleva, Natalia; Basova, Elena; Borovichev, Evgeny; Melekhin, Aleksei (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2016)
Northern taiga and mountain birch forests were investigated on the slopes of Monche tundra and Khibiny Mountains (Murmansk Region, Russia) oriented towards Lake Imandra under long-term air-borne pollution from the metal processing industry. The subject of the study was the species composition and typological diversity of vegetation along the pollution gradient at different altitudes above sea level. Three zones were distinguished – impact zone, buffer zone, and unpolluted zone as the control, 166 relevés were included in the classification that resulted in 15 groups of associations. The groups of associations were characterized; the area occupied and the proportion in the plant cover were given based on remote sensing data. Changes in plant diversity along the pollution gradient were assessed using the average number of species per 400 m2, Sørensen index, Whittaker index, as well as Shannon index. The activity of species (sensu Malyshev) was determined in groups of associations, and cluster analysis (with Euclidean distance) was undertaken to assess the similarity between the groups of associations. In the tree layer, conifers were replaced with small-leaved species, and the structure of mountain taiga on the lower and middle parts of the slopes was significantly transformed compared to mountain birch forest. On the other hand, the composition of the field layer changed towards the pollution source in the mountain birch forest more essentially than in mountain taiga. The most essential were changes of the diversity and abundance of mosses and lichens in the ground layer. The species diversity (mainly of vascular plants) increased in the buffer zone of mountain taiga due to the advance of adventitious species atypical of the zonal communities. This increase apparently represents an adaptive response of the damaged ecosystems. Green mosses were substituted by liverworts and Pohlia mosses towards the pollution source, fruticose lichens – by crustose lichen, which is considered as an adaptation to contamination at the level of phytocoenoses. The typological diversity slightly increased towards the pollution source in the mountain taiga zone, and peaked in the buffer zone. The boundary between mountain taiga and mountain birch forest has shifted to a lower altitude, towards the pollution source, as illustrated by fragments of the vegetation map. This is considered to be an adaptation to the environmental damage at the level of complexes of phytocoenoses.